Restructuring air transport to meet the needs of the Southern African development community - Muvingi, Onai (Cranfield University, 2012)
An efficient air transport system is an important part of social and economic development of Southern African Development Community (SADC). Efficient intra-SADC air service connections enhance regional integration, access to the global economy, international tourism and contribute towards the vision to establish the African Economic Community by 2034. SADC, in July 1998, embarked on liberalisation of the regional civil aviation sector in order to enhance the efficiency of air transport services. In the United States of America and European Union, the liberalisation of air transport has transformed civil aviation networks. The fragmentation of air service connections on the intra-SADC network in the midst of the liberalisation process is symptomatic of a poor implementation strategy coupled with air transport market imperfections. The purpose of this thesis is to examine, understand and explain the factors that influence the disintegration of the intra-SADC air transport network .The aim is to identify how regional air transport services can be transformed to meet the social and economic demands of the region. This research adopts network theory, as the conceptual framework of the investigation. Assuming a graph approaching maximal connection as the sought after state of affairs for SADC; this study benchmarked the post liberalisation network structure to the regional economic communities of ASEAN and MERCOSUR. The aim of the benchmarking is to identify the extend of the differences in air transport network in those two regions, resulting from the policies adopted and to establish how the SADC policies may be improved and implemented more efficiently. The findings of the study are that, in comparison to the two developing regions, SADC’s liberalisation measures have failed. The study developed and evaluated an econometric model which analysed demand patterns on the intra-SADC passenger air transport network. Although low levels of passenger demand seem to characterise the majority of SADC city-pairs, the study identified nodes with sufficient demand to justify direct connections which would in turn reduce network fragmentation. This research also establishes that the absence of a realistic detailed roadmap, an ill-defined programme of action and inadequate resources contributed to the failure of SADC’s liberalisation strategy. In its final sections, this study proposes an ideal demand-driven network configuration and offers specific recommendations to SADC member states for that network to be functional. The proposed network improves network connectivity from the current poor levels, where a connectivity measure of 15% suggests underdevelopment, to levels over 40%. The study however, acknowledges that air transport liberalisation does not necessarily guarantee equitable distribution of network efficiency in developing regions. There are communities that cannot sustain commercially viable air service connections without economic subvention, probably in the form of the Public Service Obligation (PSO) programme adopted in the EU.
Keywords: Network analysis; graph theory; graph theory; benchmarking; gravity model